Efek Senyawa Saponin pada Sapindus rarak dengan Pakan Berbasis Jerami Padi dalam Mitigasi Gas Metana - Nanang Krisnawan; Asep Sudarman; Anuraga Jayanegara; Yeni Widyawati (Jurnal Ilmu Pertanian Indonesia, 2015)
The objective of the research was to study saponin in Sapindus rarak were added to the diet of rice straw ammoniation (20 & 40%), related to the effect in reducing methane emissions of ruminants and pattern of rumen fermentation were tested by in vitro. Completly randomized block design with four treatments and four replications was used. Variables measured were gas production total, methane production, dray matter digestibility (DMD), N-ammonia, VFA total, VFA partial, and population of protozoa. The results showed that the addition saponins in S. rarak as a source of rice straw ammoniation significant effect (P<0.05) of the total gas production, methane production, dray matter digestibility (DMD), N-ammonia, VFA partial, and population of protozoa. S. rarak use as a source of saponins with a dose of 20% on rice straw ammoniation was able to reduce methane gas production drop in gas production total, concentration of N-ammonia, and  protozoa population.